Metacognitive strategies, writing self-efficacy and writing anxiety in different learning modes: a two-wave longitudinal model - Shen, Xiaolei; Ismail, Lilliati; Jeyaraj, Joanna Joseph; Teng, Mark Feng (Elsevier, 2024)
Writing difficulties stemming from cognitive and emotional factors contribute to heightened levels of writing anxiety. Studies have highlighted the pivotal roles of metacognitive strategies and writing self-efficacy in predicting writing anxiety, particularly in cross-sectional analyses. However, how these constructs interact with writing anxiety in longitudinal studies remains relatively understudied. Therefore, it is essential to develop a comprehensive understanding of metacognitive strategies and self-efficacy to effectively mitigate writing anxiety for English as a foreign language (EFL) learners. We administered three questionnaires on metacognitive strategies use, writing self-efficacy, and writing anxiety to 301 participants across online and offline learning modes. We employed a two-wave longitudinal model to explore the possible temporal correlations. The findings indicated negative reciprocal correlations between the metacognitive strategies use in writing context and writing anxiety. Writing self-efficacy positively predicted metacognitive strategies use and negatively predicted writing anxiety. Writing self-efficacy did not act as a moderator in the relationship between metacognitive strategies use and writing anxiety, implying that the impact of metacognitive strategies use on anxiety levels remains consistent regardless of learners' self-efficacy. The current study offers valuable insights to EFL educators on integrating metacognitive strategies and self-efficacy to mitigate learners' writing anxiety.